simplify

5g-2g

pxp

3p=4p

exfx5

d+d+d+d+d

y square 2 +ysquare 2

4(3a-7)

txt square 2

m square 5 : msquare 3

a+a+a+a

3xbx4

simplify completely

4a+5b+-2a+b

factorise xsquare2 -6x

Simplify

5g-2g =3g

pxp= p^2

3p-4p=0

p(3-4)=0

p =0

5ef

d+d+d+d+d=5d

y square 2 +ysquare 2 =2y^2

4(3a-7)=12a-28

(t^2)^2= t^4

m square 5 : msquare 3 m^5 /m^3 = m^(5-3) = m^2

a+a+a+a =4a

3xbx4 = 12b

4a+5b+-2a+b = 2a+6b

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up